2017
DOI: 10.1016/j.foodres.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Taste receptors in the gut – A new target for health promoting properties in diet

Abstract: These receptors are involved in an intricate signalling network for monitoring of taste and nutrient intake, homeostasis and energy metabolism, and they are also an early warning system for toxic substances in our diet. Especially the receptors for bitter taste provide a new possibility to activate a number of health related signalling pathways, already at low concentrations of the active substance, without requiring uptake into the body and transport via the circulation. When ligands bind to these receptors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 131 publications
0
20
0
Order By: Relevance
“…36 Our slightly bitter tasting rice peptides may have addressed intestinal G-protein-coupled receptor based signaling elements. 37 These bitter receptors were described to activate multiple health related signaling pathways, at low concentrations of the active substance, without requiring uptake into the body. Similarly, chemokine receptor type 9 (CCR9), also designated CDw199, and chemokine receptor 3 from the CXC chemokine receptor family (CXCR3) are expressed in the small intestine and constitute principal targets for anti-chemokine therapy in inflammatory bowel disease.…”
Section: Early Clinical Observationsmentioning
confidence: 99%
“…36 Our slightly bitter tasting rice peptides may have addressed intestinal G-protein-coupled receptor based signaling elements. 37 These bitter receptors were described to activate multiple health related signaling pathways, at low concentrations of the active substance, without requiring uptake into the body. Similarly, chemokine receptor type 9 (CCR9), also designated CDw199, and chemokine receptor 3 from the CXC chemokine receptor family (CXCR3) are expressed in the small intestine and constitute principal targets for anti-chemokine therapy in inflammatory bowel disease.…”
Section: Early Clinical Observationsmentioning
confidence: 99%
“…For example, changes in taste acuity are commonly observed in adult cancer patients, presumably because of malnutrition and emotional stress caused by cancer and treatment (Nagai, Kubota, Adachi, Watanabe, & Takeshita, ). Bitter taste receptors were also found in the gastrointestinal tract (Ekstrand et al, ). A chronic inflammatory process may reduce the sensitivity of the receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The increased consumption of sweet products by obese children is caused by their high preferences and low sensory sensitivity to sweetness (Laffitte, Neiers, & Briand, ; Sobek & Mazur, ). The receptors of sweet, bitter, and umami tastes have been identified in different organs (gastrointestinal tract, heart, brain, bladder, nasal respiratory epithelium, and kidney) and in some specific cells, such as B lymphocytes, but further research is necessary to investigate their influence (Ekstrand, Young, & Rasmussen, ; Laffitte et al, ). Many studies have shown that medical conditions affect the sense of taste, for example, endocrine, neurological, and nutritional factors (deficiency of niacin and vitamin B12), and viral infections (Boyce & Shone, ; Cermak, Curtin, & Bandini, ; Kato & Roth, ; Santos, Santos Marreiros, Soares de Oliveira, Torres de Freitas, & Clímaco Cruz, ; Schiffman & Graham, ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of NNS are artificially synthesized (hence, artificial sweetener), however, some are derived from natural sources; steviol glycosides is a natural extract from Stevia rebaudiana (2). All of these compounds stimulate oral sweet taste perception through activation of the sweet taste receptor; a heterodimer of type 1 taste receptor 2 (T1R2)/type 1 taste receptor 3 (T1R3) (3). The T1R2/T1R3 sweet taste receptor is expressed not only in the oral cavity but also in several gut cells, indicating a role in gut nutrient sensing (3).…”
Section: Introductionmentioning
confidence: 99%
“…All of these compounds stimulate oral sweet taste perception through activation of the sweet taste receptor; a heterodimer of type 1 taste receptor 2 (T1R2)/type 1 taste receptor 3 (T1R3) (3). The T1R2/T1R3 sweet taste receptor is expressed not only in the oral cavity but also in several gut cells, indicating a role in gut nutrient sensing (3). In this review, recent investigations into the physiological response to activation of the T1R2/T1R3 receptor in the oral cavity and gut in response to both sugars and sweeteners are summarised and discussed.…”
Section: Introductionmentioning
confidence: 99%